2004
DOI: 10.2135/cropsci2004.0474
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and Water Availability Effects on Water-Use Efficiency in Wheat

Abstract: purposes and to adopt management practices that allow WUE to be maximized. In Argentina, wheat (Triticum aestivum L.) is cropped over a wideIn Argentina, wheat is mainly cropped from 32 to range of climatic conditions. Considerable variability in the ratio of 39ЊS and 57 to 63ЊW (Hall et al., 1992). Considerable dry weight produced per unit of transpired water, usually referred to variability in climatic conditions and WUE is expected as water-use efficiency (WUE), is expected as variation in climatic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Often its effectiveness could not be observed if stubbles were not retained (O'Leary and Connor, 1997). Nevertheless, our study showed that fallow treatment was among one of the most efficient in water use with a WUE of 8.4 kg/(ha mm À1 ) average over two years and was similar to findings in other dryland regions of the world (Zhang et al, 1998;Abbate et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Often its effectiveness could not be observed if stubbles were not retained (O'Leary and Connor, 1997). Nevertheless, our study showed that fallow treatment was among one of the most efficient in water use with a WUE of 8.4 kg/(ha mm À1 ) average over two years and was similar to findings in other dryland regions of the world (Zhang et al, 1998;Abbate et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…The reduction of water potential is also greatly dependent on crop species, varieties, and level of stress. However, Abbate et al [72] and Subramanian et al [73] reported higher WUE in wheat and tomato under drought than well-watered controls, which was mainly due to the reduced transpiration rates under drought. For instance, drought-tolerant genotypes maintained a higher leaf water potential for longer and wilted later than sensitive genotypes upon exposure to drought [69].…”
Section: Plant---water Relationsmentioning
confidence: 94%
“…However, any positive effects of warmer temperature on nutrient capture are dependent on adequate soil moisture. If under dry conditions higher temperatures result in extreme vapor pressure deficits that trigger stomatal closure (reducing the water diffusion pathway in leaves) (Abbate et al 2004), then nutrient acquisition driven by mass flow will decrease (Cramer et al 2009). Temperature driven soil moisture deficit slows nutrient acquisition as the diffusion pathway to roots becomes longer as ions travel around expanding soil air pockets (Brouder and Volenec 2008).…”
Section: Effects Of Temperature On Nutrient Acquisitionmentioning
confidence: 99%